Modelling the Dividend-Price Ratio: The Role of Fundamentals Using a Regime-Switching Approach - Steen Nielsen; Jan Overgaard Olesen (Copenhagen Business School (CBS), Department of Economics, 2001)
Using annual data over the post-World War I-period, we estimate a fundamentals-based empirical model for the dividend-price ratio of Danish stocks. The key fundamentals-variable is a time-varying discount rate, decomposed into time-varying measures for the growth-adjusted real interest rate and the risk premium on stocks. In addition, the model includes real dividends and the lagged dividend-price ratio as explanatory variables. Results show that the model suffers from structural breaks over the sample. Using a two-state regime-switching approach to capture non-modeled shifts in the economic environment, we find that all fundamentals are highly significant in at least one regime and, moreover, obtain a good fit. The model identifies two very persistent regimes characterized by a `low', respectively, `high' dividend-price ratio.
hdl:10398/7556
Keywords: G19; 330; Dividend-price ration; Stocks; Denmark